Dog Exposure During the First Year of Life and Type 1 Diabetes in Childhood - Wernroth, Mona-Lisa (JAMA Pediatr, 2017)
IMPORTANCE: The association between early exposure to animals and type 1 diabetes in childhood is not clear. OBJECTIVE: To determine whether exposure to dogs during the first year of life is associated with the development of type 1 diabetes in childhood. DESIGN, SETTING, AND PARTICIPANTS: A nationwide cohort study utilizing high-quality Swedish national demographic and health registers was conducted. A total of 840 593 children born in Sweden from January 1, 2001, to December 31, 2010, were evaluated. Type 1 diabetes was identified using diagnosis codes from hospitals and dispensed prescriptions of insulin. Cox proportional hazards regression models were used to assess the association between exposure to dogs and risk of type 1 diabetes in childhood. The possible association was further investigated by performing dose-response and breed group–specific analyses. The cohort was followed up until September 30, 2012. Data analysis was conducted from October 15, 2015, to February 8, 2017. EXPOSURES: Having a parent who was registered as a dog owner during the child’s first year of life. MAIN OUTCOMES AND MEASURES: Childhood-onset type 1 diabetes. RESULTS: Of the 840 593 children reviewed, 408 272 (48.6%) were girls; mean (SD) age at diagnosis of type 1 diabetes was 5.1 (2.6) years. Dog exposure was identified in 102 035 children (12.1%). Follow-up started at age 1 year, and the children were followed up for as long as 10.7 years (median, 5.5 years). During follow-up, 1999 children developed type 1 diabetes. No association was found between exposure to dogs (adjusted hazard ratio [HR], 1.00; 95% CI, 0.86-1.16) and type 1 diabetes in childhood. The size of the dog (adjusted HR per 10-cm increase in height, 0.96; 95% CI, 0.86-1.06) or number of dogs in the household (1 dog: adjusted HR, 1.07; 95% CI, 0.91-1.26; 2 dogs: 0.79; 95% CI, 0.54-1.15; ≥3 dogs: 0.50; 95% CI, 0.23-1.12; compared with nonexposed children) also was not associated with type 1 diabetes risk. An analysis of children whose parent had type 1 diabetes (210 events) yielded an adjusted HR of 0.71 (95% CI, 0.43-1.17) for dog exposure. CONCLUSIONS AND RELEVANCE: In a nationwide study, no evidence supporting an association of register-derived measures of dog exposure with childhood type 1 diabetes was identified.